Preparation and characterization of PMMA-MG49-LiClO4 solid polymeric electrolyte - Su'Ait M.S.; Ahmad A.; Hamzah H.; Rahman M.Y.A. (2023)
The potential of hybrid polymer 49% poly(methyl methacrylate)-grafted natural rubber (MG49) and poly(methyl methacrylate) (PMMA) as a polymer host in solid polymer electrolyte film for rechargeable battery systems has been investigated. The hybrid films were prepared by the solution casting technique. The ionic conductivity was investigated by alternating current electrochemical impedance spectroscopy. The highest conductivity was 1.47 10 -8 S cm-1 at 20 wt% of LiClO4. The observation on structural studies performed by x-ray diffraction showed that the crystallinity phase is reduced at the highest conductivity. Fourier transform infrared spectroscopy analysis showed that the interaction between lithium ion and oxygen atoms occurred at carbonyl (C=O) and ether (C-O-C) groups. 2009 IOP Publishing Ltd.